Altruism or trade motive: what determines China’s financial aid to African oil exporting countries? - Gold, Kafilah; Rasiah, Rajah; Kwek, Kian Teng; Yusuf, Hammed; Musibau, Hammed; Muhammad, Murtala (Journal of Business Economics and Management, 2021)
Indeed, China’s ascent is significantly changing the landscape in aid-donor and aid-recipient relationship for African countries, despite the changes, empirical studies on the determinant and motive is lacking. Therefore, this paper examines the determinants of China’s financial aid to oil/ minerals exporting African countries. By using China’s loan data obtained from the China Africa Research Initiative, Johns Hopkins University and UN-COMTRADE product data classified into oil/ minerals, agriculture and manufacturing, this study employs fixed effects, generalised least squares and Pesaran dynamic fixed effects to analyse the motives. The results indicate that oil/minerals are not the motives behind China’s aid to Africa. However, China’s aid is driven by its manufacturing exports, suggesting that aid may be tied to trade. Also, the institutional structure enhances more financial aid to Africa. The findings of this study serve as recommendations for policymakers to improve trade policies that will enhance the sustainability of Africa’s engagement with China.